Exosomes Released From Human Bone Marrow–Derived Mesenchymal Stem Cell Attenuate Acute Graft-Versus-Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation in Mice - Li, Ke-Liang; Li, Jin-Yan; Xie, Gui-Ling; Ma, Xiao-Yan (Frontiers in Cell and Developmental Biology, 2021)
Objective: Mesenchymal stromal cells (MSCs)-derived exosomes have been applied for the treatment of several immune diseases. This study aimed to explore the effect of human bone marrow-derived mesenchymal stem cell (hBMSC)-derived exosomes on acute graft-versus-host disease (aGVHD) after allogeneic hematopoietic stem cell transplantation (HSCT). Methods: hBMSC were cultured, and the culture supernatants were then collected to prepare exosomes using total exosome isolation reagent from Invitrogen. Mouse aGVHD model was established by allogeneic cell transplantation, and injected with hBMSC-derived exosomes (Msc-exo) via tail vein. Exosomes from human fibroblast (Fib-exo) were used as the treatment control. The effects of Msc-exo on dendritic cells, CD4+ and CD8+ T cells in aGVHD mice were analyzed through flow cytometry. The impact on inflammatory cytokines was tested by ELISA. Besides, the body weight, survival rate and clinical score of treated mice were monitored. Results: Msc-exo were successfully prepared. aGVHD mice injected with Msc-exo led to 7-8 fold increase of the CD8α+ cDCs and CD11b+ cDCs compared with the controls. In addition, Msc-exo altered the T help and Treg subpopulation, and decreased the cytotoxicity and proliferation of cytotoxic T cells to favor inflammatory inhibition in aGVHD mice. Mice that received Msc-exo exhibited decreased weight loss and reduced aGVHD clinical score in a time-dependent manner as well as reduced lethality compared with Fib-exo treated or untreated control. Furthermore, the levels of IL-2, TNF-α and IFN-γ were decreased, as well as the level of IL-10 was increased after Msc-exo treatment in vivo and in vitro. Conclusions: hBMSC-derived exosomes could attenuate aGVHD damage and promote the survival of aGVHD mice by regulating the DC and T cell subpopulation and function, and lead to inhibited inflammatory response in aGVHD mice.